Herakles inside and outside the church: from the first apologists to the end of the Quattrocento - Allan, Arlene; Anagnostou-Laoutides, Evangelia ca. 20./21. Jh.; Stafford, Emma (Metaforms, 2020)
"Herakles Inside and Outside the Church: from the first Apologists to the Quattrocento explores the reception of the ancient Greek hero Herakles (the Roman Hercules) in the predominantly Christian cultures which succeeded classical antiquity in Europe. Each chapter takes a particular literary or visual incarnation, grappling with the question of the hero's significance within the early Church, in less formal contexts, and beyond Christendom in his unexpected role as Buddha's companion in Gandharan art. The volume is one of four to be published in the Metaforms series examining the extraordinarily persistent role of Herakles-Hercules in western culture up to the present day, drawing together scholars from a range of disciplines to offer a unique insight into the hero's perennial appeal"--